Video from Tokyo to Fukui and Kyoto (New York : The Museum of Modern Art, 1979)
Mako Idemitsu ; Nobuhiro Kawanaka - Hakudo Kobayashi ; Akira Kurosaki ; Toshio Matsumoto ; Kyoko Michishita ; Tsuneo Nakai ; Kou Nakajima ; Fujiko Nikaya ; Hitoshi Nomura
Video from Tokyo to Fukui and Kyoto, The Museum of Modern Art, New York, April 19 - June 19, 1979 ; Long Beach Museum of Art, Long Beach, California, Juen 24 - August 5, 1979 ; Vancouver Art Gallery, Vancouver, July 20 - August 6, 1979 ; The Prefectural Museum of Art, Fukui, April 1980
boek
Keywords: Japan